2001
DOI: 10.1210/jcem.86.11.8035
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Obesity and Glycemic Control on Endothelial Activation in Patients with Type 2 Diabetes

Abstract: The aims of this study were to elucidate the factors that contribute to endothelial activation and fibrinolytic abnormalities in patients with poorly controlled type 2 diabetes and to determine whether improved glycemic control reduces endothelial activation. Adhesion molecules [E-selectin, intracellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1], von Willebrand factor, total nitric oxide (NO), endothelin-1, tissue plasminogen activator, and plasminogen activator inhibitor-1 were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 39 publications
6
34
0
Order By: Relevance
“…As expected from previous studies [5][6][7][8][9][10][11], plasma vWf, sE-sel and TF were higher in patients compared with controls ( Table 2). There were no significant differences in plasma vWf and sE-sel between those with CVD and without overt CVD.…”
Section: Plasma Vwf Se-sel and Tfsupporting
confidence: 89%
See 2 more Smart Citations
“…As expected from previous studies [5][6][7][8][9][10][11], plasma vWf, sE-sel and TF were higher in patients compared with controls ( Table 2). There were no significant differences in plasma vWf and sE-sel between those with CVD and without overt CVD.…”
Section: Plasma Vwf Se-sel and Tfsupporting
confidence: 89%
“…Indeed, increased levels of circulating sE-sel and vWf are also associated with increased cardiovascular morbidity and mortality, albeit predominantly in the non-diabetic population [2][3][4][5][6]. However, raised levels of sE-sel and vWf have also been consistently shown in patients with diabetes mellitus [5,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Thus, an imbalance between the endothelial and insulin-dependent pathways (MAPK-dependent and PI3K-dependent signals) might be involved in the endothelial derangements successively participating in the metabolic disturbances with insulin resistance. 5,12 These specific pathophysiological links suggest the strict relationship between metabolic and cardiovascular diseases.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…8) Serum concentrations of soluble adhesion molecules such as soluble endothelial leukocyte adhesion molecule (ELAM-1, E-selectin), intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) are related to the degree of insulin resistance and hyperglycemia in patients with type 2 diabetes. 9,10) Incubation of human umbilical vein endothelial cells (HUVEC) in culture media containing high glucose enhances the expression of cell surface adhesion molecules through a process that involves nuclear factor-kB (NF-kB), 11) protein kinase C, [12][13][14] and poly ADP ribose polymerase, 15) although the precise mechanism remains to be elucidated. In a previous report, 16) we demonstrated that glycated human serum albumin enhanced E-selectin expression on HUVEC by NF-kB and activator protein-1 (AP-1) via NADPH oxidase activation.…”
Section: Protein O-glcnacylation Is Catalyzed By O-glcnac Transferasementioning
confidence: 99%